Native bacterial strains with plant growth promotion activities isolated from Coffea spp. rhizosphere in Pichanaqui, Perú - Mario Alcarraz Curi; Vidalina Heredia Jiménez; Jean Paul Julian Ibarra (Biotecnología Vegetal, 2019)
The deterioration of the soil and the demand for organic coffee, makes it necessary to find alternatives to improve its productivity and quality, so the objective of the research was to select native bacterial strains from coffee plants rhizosphere with plant growth promotion activities. Bacteria were isolated from the rhizosphere of coffee crops in the Pichanaqui district, Chanchamayo Province, Junín, Peru. The plant growth promotion activities were in vitro determined for strains obtained through tests of atmospheric N2 fixation, phosphate solubilization and indole acetic acid (IAA) production. The best-performing strains were molecularly identified through the 16S rRNA gene. Twelve bacterial strains were selected. All strains fixed atmospheric N2 , 83.3% produced IAA and 75% solubilized phosphates. The presence of three genera was identified: Azospirillum ,Pseudomonas and Burkholderia . Several strains have more than one activity to promote plant growth. Especially, Azospirillum amazonense 1I (net nitrogen fixation 2.05 mg l-1 , 66.03 μg ml-1 IAA production and phosphate solubilization). This makes them potential biofertilizers for the coffee crop (Coffea spp.).